The Role of Green Accounting in Enhancing Business Sustainability: A Case Study of Renewable Energy Companies - Amos Lukas; Akenji Cliford Fru-Ngongban; Hafiz Ali Raza (SINOMIKA JOURNAL: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2025)
This study explores the role of green accounting in enhancing business sustainability, specifically within renewable energy companies. As environmental concerns increase globally, businesses are under growing pressure to adopt sustainable practices, with green accounting serving as a critical tool in this transformation. Green accounting involves integrating environmental costs into traditional financial reporting systems, allowing companies to better track their environmental impact, improve resource efficiency, and contribute to long-term sustainability. This research investigates how renewable energy companies implement green accounting practices and assesses the impact of these practices on their sustainability performance. Using a qualitative approach, the study examines multiple case studies from companies in the renewable energy sector, highlighting both the benefits and challenges of adopting green accounting. The findings suggest that companies with comprehensive green accounting systems not only achieve better environmental outcomes but also improve their relationships with stakeholders, attract investment, and gain a competitive advantage. However, the study also identifies significant barriers, including the lack of standardized reporting frameworks and internal resistance to change. The research concludes that the widespread adoption of green accounting is essential for advancing sustainability in the renewable energy sector and offers practical recommendations for overcoming implementation challenges.